Precision measurement of net-proton-number gluctuations in Au+Au collisions at RHIC - Aboona, Bassam; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physical review letters, 2025)
We report precision measurements on cumulants (𝐶𝑛) and factorial cumulants (𝜅𝑛) of (net) proton number distributions up to fourth order in Au+Au collisions over center-of-mass energies √𝑠𝑁⁢𝑁=7.7-27 GeV from phase II of the Beam Energy Scan program at RHIC. (Anti)protons are selected at midrapidity (|𝑦| <0.5) within a transverse momentum range of 0.4<𝑝𝑇<2.0 GeV/𝑐. Relative to various noncritical-point model calculations and peripheral collision 70%-80% data, the net proton 𝐶4/𝐶2 measurement in 0%-5% collisions shows a minimum around 19.6 GeV for significance of deviation at ∼2-5⁢𝜎. A minimum in 𝐶4/𝐶2 with respect to a noncritical baseline is expected to be a characteristic feature of the signature associated with a critical point in the QCD phase diagram. In addition, deviations from noncritical baselines around the same collision energy region are also seen in proton factorial cumulant ratios, especially in 𝜅2/𝜅1 and 𝜅3/𝜅1. Dynamical model calculations including a critical point are called for in order to understand these precision measurements.
Veröffentlicht: 29. September 2025
*STAR Collaboration: B.E. Aboona, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen [und 367 weitere Personen]
Gesehen am 20.02.2026